A structural break in the effects of Japanese foreign exchange intervention on yen/dollar exchange rate volatility - Eric Hillebrand; Gunther Schnabl (European Central Bank (ECB), 2006)
While up to the late 1990s Japanese foreign exchange intervention was fully sterilized, Japanese monetary authorities left foreign exchange intervention unsterilized when Japan entered the liquidity trap in 1999. According to previous research on foreign exchange intervention, unsterilized intervention has a higher probability of success than sterilized intervention. Based on a GARCH framework and change point detection, we test for a structural break in the effectiveness of Japanese foreign exchange intervention. We find a changing impact of Japanese foreign exchange intervention on exchange rate volatility at the turn of the millennium when Japanese foreign exchange intervention started to remain unsterilized.
Keywords: E58; F31; F33; G15; 330; Change Point Detection; Exchange rate volatility; foreign exchange intervention; GARCH; Japan; Structural Breaks; Wechselkurspolitik; Wechselkurs; Volatilität; ARCH-Modell; Strukturbruch; Yen; US-Dollar; Japan